A method for evaluation of uncertainties of noise parameter measurement - Marek Schmidt-Szałowski; Wojciech Wiatr (Journal of Telecommunications and Information Technology, 2002)
The assessment of uncertainties of a two-port noise parameters measurement, presented in the paper, relies on modeling of sources of errors and an investigation of propagation of the errors through a measurement system. This approach is based on a simplified additive error model and small-change sensitivity analysis. The evaluated uncertainties agrees with those observed in experiments. This method may be implemented in automatic noise measurement systems for on-line uncertainty assessment and for optimization of the design of an experiment.